Developing of a gis tool to estimate the repair cost of buildings due to earthquake effects in Peru - Morales, Jorger Manuel (2019)
Along the history, Peru have suffered many human and material losses due to the effects of natural hazards, particularly earthquakes, only in the capital city, Lima, three large earthquakes have occurred in the last century, in 1940, 1966 and 1974. But hazards itselves would not become disasters without a vulnerable population, which is the case of Peru, where the growing and developing of cities has lacked of any planification and it has been disordered, with people building without following the current regulatory framework that ensures good structural behavior during a severe seismic event. For those reasons, among others, is needed a tool that permits the identification of highly risk areas in case of earthquakes. The current study proposes an automated system on a GIS platform that allows to estimate the damage effects of earthquakes in buildings, showing the results as repairing costs. Using as basis Geotechnical information like peak ground acceleration (PGA) or Spectral acceleration (Sa), urban cadaster information (material of the building, the soil, the number of stories, etc.) and using the outputs of experimental tests and analytic simulations for different building types used in Peruvian territory, like masonry buildings, reinforced concrete buildings, adobe or quincha buildings, wooden buildings among others. This tool would allow stakeholders to have an idea of the expected damage for the next quake and would help them to take actions before the event, actions like retrofitting or relocating buildings.